2021
DOI: 10.3390/polym14010100
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran-Based Bioplastics: Effects of Biopolymer Fractions on Their Mechanical, Functional and Microstructural Properties

Abstract: Rice bran is an underutilized by-product of rice production, containing proteins, lipids and carbohydrates (mainly starches). Proteins and starches have been previously used to produce rice bran-based bioplastics, providing a high-added-value by-product, while contributing to the development of biobased, biodegradable bioplastics. However, rice bran contains oil (18–22%), which can have a detrimental effect on bioplastic properties. Its extraction could be convenient, since rice bran oil is becoming increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The rest of the unidentified components were assumed to be fibers present in the composition of these fruits. These fibers could serve as filler reinforcing the bioplastics [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The rest of the unidentified components were assumed to be fibers present in the composition of these fruits. These fibers could serve as filler reinforcing the bioplastics [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, rice bran can be processed by injection molding, and the properties of the resulting bioplastics can be tuned by the processing conditions and the addition of plasticizers, as well as by the blend components and the pretreatments of the byproduct. In fact, defatted rice bran results in bioplastics with higher viscoelastic moduli and higher performance compared to untreated bran, whereas, in contrast, lipids provide a plasticizing effect …”
Section: Upgrading Food Protein Waste Beyond the Food-value Chainmentioning
confidence: 99%
“…In fact, defatted rice bran results in bioplastics with higher viscoelastic moduli and higher performance compared to untreated bran, whereas, in contrast, lipids provide a plasticizing effect. 543 5.1.6. Bioplastics from Denatured Proteins.…”
Section: Bioplasticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the use of rice bran as an ingredient in animal feed and in human food products, such as cereals, bread, and snacks [ 16 ]. It has also been studied for its potential use in various industrial applications, such as in the production of biofuels, bioplastics, and nutraceuticals [ 17 , 18 , 19 ]. The use of rice starch as a pharmaceutical excipient has long been established.…”
Section: Introductionmentioning
confidence: 99%